Ultrasound-Guided Peripheral Nerve Blocks (Springer International Publishing, 2018)
This book offers a comprehensive but straightforward, practical handbook on ultrasound (US)-guided nerve blocks. It presents the normal US anatomy of peripheral nerves, clinical aspects of nerve entrapment and different procedures / techniques for each block. Axial or peripheral chronic radicular pain can be particularly severe and debilitating for the patient. The aim of treatment is to provide medium-/ long-term pain relief, and consequently to restore function. The therapeutic nerve block, performed with a perineural injection of anaesthetic, steroid or painkiller, is generally used once conservative treatments have proven unsuccessful and is aimed to avoid surgical options. Ultrasound guidance, offering the direct and real-time visualization of the needle and adjacent relevant anatomic structures, significantly increases the accuracy and safety of nerve blocks reducing the risk of intraneural or intravascular injection and the potential damage to the surrounding structures, but also enhances the efficacy of the block itself, reducing its onset and drug doses. This practical volume addresses the needs of physicians dealing with pain management, e.g. anaesthesiologists, radiologists, orthopaedists and physiatrists, with various levels of experience, ranging from physicians in training to those who already perform peripheral nerve blocks with traditional techniques and who want to familiarize with US guided procedures.